Directions Of Ore Fluid Flow In The Southeast Missouri Lead-Zinc District As Inferred From Asymmetrical Distributions Of Orebodies Around Precambrian Knobs And From Mineral/Metal Zoning Patterns - R. D. Hagni (Society for Mining, Metallurgy & Exploration, 2006)
Introduction The ore deposits of the Viburnum Trend in the Southeast Missouri Lead District constitute the world's largest lead producing district. Six or seven mines currently are in production in the Viburnum Trend. The principal minerals are few in number, simple in composition, and form simple superposition and replacement textures. The economically valuable minerals in the typical lead-zinc ores of the Viburnum Trend are the sulfides, galena, sphalerite, chalcopyrite, and siegenite. The most abundant gangue minerals are dolomite, marcasite, pyrite, calcite, quartz, and dickite. Four concentrates, lead, zinc, copper, and cobalt are produced from the ores, and they contain an interesting suite of trace elements, of which silver and cadmium are recovered at the smelter and refinery.1 Emphasis is given here to the variations in directions of ore fluid flow based upon interpretations of the positions of orebodies due to the ore fluids being impeded by Precambrian basement relief and upon patterns of ore mineral/metal zoning. The Precambrian basement relief and Lamotte Formation pinchout has exerted an important control upon the specific locations of orebodies in the Southeast Missouri Lead District. The locations of some orebodies along one side of Precambrian knobs or ridges strongly suggests that they are positioned on the side from which the ore fluids flowed. Other orebodies are located in positions that suggest that they formed where the ore fluids passed around or between Precambrian knobs. Patterns of mineral and/or metal zoning have been used in many mineral districts to interpret the directions of ore fluid flow. The mineral/metal zoning pattern correlates closely with that of the mineral paragenesis. The earliest deposited minerals tend to be deposited nearest to the source, the later deposited minerals next closest to the source, and the latest deposited minerals furthest from the source. In the Southeast Missouri Lead District, it is interpreted here that the early-deposited copper-rich ores are closest to the source of the ore fluids, the subsequently-deposited zinc-rich ores are next closest to the source, and iron-rich ores are furthest from the source.